Semiotics of Characters in the Novel Rangsang Tuban by Padmasusastra - Maratuzzakiyah; Dhoni Zustiyantoro (Universitas Negeri Semarang, 2024)
This research is motivated by the unique names in the Javanese language that have the meaning of water used by Padmasusastra to name the characters in the novel Rangsang Tuban. The data of this research are the names of the novel’s characters and the sentences in the novel’s text. The names have implied meanings related to water and are connected to the novel’s character, setting, and plot. The data collection technique used is reading and recording to obtain narrative units. This study aims to explain the signs and meanings when naming each character in the novel Rangsang Tuban by Padmasusastra. The theory used in this research is dynamic structuralism, which uses Charles Sanders Peirce’s semiotic approach. Primary data sources were obtained from the novel Rangsang Tuban by Padmasusastra, published in 2013. Secondary data sources are in the form of supporting articles. The concept of semiotics of signs in the form of character names and markers in the form of meaning and data proves the existence of this meaning. The method used is a qualitative description that describes the discussion based on literary works. Based on the semiotic analysis of character naming in the novel Rangsang Tuban, it can be seen: (1) a Description of the meaning of the name that describes the character, (2) a Description of the meaning of the name that shows the setting of the place and the flow of events in the story. The implications of this research contribute to the development of research theory with the concept of Peirce semiotics. They can be an analytical tool for studying modern Javanese literature, including novels.